Students Perception And Teachers Preference In English Grammar Teaching Methods In Senior High School - Atini, Atini; Taridi, Muhamad (JESS (Journal of Education on Social Science); Vol 10 No 2 (2026): Public Participation in Public ServiceDO - 10.24036/jess.v10i2.670, 2026)
This study aims to analyze students’ and teachers’ preferences for learning methods in English Grammar in High School 3, Jambi City. Learning English grammar is often considered complex and less interesting by learners, so a well-designed pedagogical approach is needed to make the learning process more effective. This study uses a mixed-method approach. Quantitative Data were collected through the completion of questionnaires by 38 students of Class X, and qualitative data were collected through in-depth interviews with 2 teachers of Class X, Class observation, and documentation. Subjects consisted of students and teachers of English class X in SMA Negeri 3 Jambi City. The results showed that students responded positively to eight teaching methods. Then teachers tend to apply a communicative and deductive approach, using English as the main language of instruction, employing realia and diverse media, and adjusting error-correction strategies to students’ needs. It found a gap between current teacher practices and students’ preferences for a more interactive, emotionally supportive learning environment. This study emphasizes the importance of aligning grammar-learning methods with students’ expectations to enhance teaching effectiveness in EFL contexts.